The Role of Marketing Economic Management in Supporting the Achievement of the Sustainable Development Goals (SDGS) - Nedi Rinaldi; Mardia Pulungan; Arian Denopan; Muhammad Ilyas (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The achievement of the Sustainable Development Goals (SDGs) requires the active involvement of the economic sector, including the implementation of sustainable-oriented marketing economics management practices. Marketing is no longer understood merely as a commercial activity, but as a strategic instrument capable of integrating economic, social, and environmental objectives within the framework of sustainable development. This study aims to analyze the role of marketing economics management in supporting the achievement of the SDGs. The research employs a qualitative approach through a systematic literature review of reputable international journal articles indexed in Scopus, Web of Science, and Google Scholar. The data were analyzed using thematic analysis to identify patterns, concepts, and the strategic contributions of marketing economics management to sustainable development goals. The findings indicate that marketing economics management plays a significant role in promoting sustainable economic growth, shaping responsible consumer behavior, and integrating social and environmental values into business strategies. Furthermore, sustainable marketing practices enhance business competitiveness, corporate social legitimacy, and the quality of economic growth. This study concludes that marketing economics management constitutes a strategic pillar in achieving the SDGs and should be systematically integrated into business and development policies.